KORELASI REGISTRASI TENAGA KESEHATAN TERHADAP KOMPETENSI TENAGA KESEHATAN DALAM PELAYANAN KESEHATAN MASYARAKAT - Sri Retno Widyorini (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Health as an element of general welfare must be realized through various health efforts in the framework of comprehensive and integrated health development supported by a national health system. Health workers who will provide health services to the community must have a STR (Registration Certificate) issued by the government as the person in charge of public health services. Doctors as one of the health workers areresponsible for providing health services in accordance with applicable laws andregulations, namely Law Medical Practice and Doctor's Code of Ethics. Doctors whopractice health services to the community in hospitals are bound by the Doctor's Code of Ethics and are also bound by Hospital By Laws as an internal regulation of the hospital.